2020
DOI: 10.1088/1361-6595/ab74b6
|View full text |Cite
|
Sign up to set email alerts
|

Background pressure effects on ion dynamics in a low-power magnetic nozzle thruster

Abstract: The effect of background neutral density on the ion acceleration region of a magnetic nozzle thruster is investigated through a combination of theoretical models and experiment. Ion velocities are measured in the magnetic nozzle using laser induced fluorescence as the background pressure is raised from 0.98 to 26 μTorr-Xe. It is found that the ion velocity exiting the acceleration region decreases from roughly 12 800 to 10 200 m s −1 as background pressure is increased corresponding to a drop in accelerated io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…This phenomenon is more acute inside a vacuum facility due to the additional effect of the background pressure. Other experiments have shown a significant decrease of ion energy (and thus thrust) as the background pressure is increased due to both new born ions and resistive deceleration [410]. The assessment of the effect of ion-neutral collisions in the beam expansion and the thrust would require a dedicated research, since other configurations have shown that for specified potential drop, ion-neutral collisions during the ion acceleration can increase the thrust [411], [412].…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…This phenomenon is more acute inside a vacuum facility due to the additional effect of the background pressure. Other experiments have shown a significant decrease of ion energy (and thus thrust) as the background pressure is increased due to both new born ions and resistive deceleration [410]. The assessment of the effect of ion-neutral collisions in the beam expansion and the thrust would require a dedicated research, since other configurations have shown that for specified potential drop, ion-neutral collisions during the ion acceleration can increase the thrust [411], [412].…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…The thruster efficiencies for the three solenoid currents are calculated from the energy losses in the magnetic nozzle rf plasma thruster using Equation (7). The thruster efficiencies are 2.1%, 27.4%, and 45.0% for the solenoid currents of 0.1, 0.4, and 2.0 kA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic nozzle radiofrequency (rf) plasma thrusters have been developed worldwide for future high-power electric propulsion systems [1][2][3][4][5][6][7]. The main components of the magnetic nozzle rf plasma thruster are an rf antenna, a dielectric tube, and the solenoid.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling of plasma flow with neutrals is important in many fusion 3 and plasma thruster applications [31][32][33] . Model equations were used to point out characteristic effects due to ionization and charge-exchange processes.…”
Section: Discussionmentioning
confidence: 99%